-4x+6=-2x+4

Simple and best practice solution for -4x+6=-2x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+6=-2x+4 equation:


Simplifying
-4x + 6 = -2x + 4

Reorder the terms:
6 + -4x = -2x + 4

Reorder the terms:
6 + -4x = 4 + -2x

Solving
6 + -4x = 4 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
6 + -4x + 2x = 4 + -2x + 2x

Combine like terms: -4x + 2x = -2x
6 + -2x = 4 + -2x + 2x

Combine like terms: -2x + 2x = 0
6 + -2x = 4 + 0
6 + -2x = 4

Add '-6' to each side of the equation.
6 + -6 + -2x = 4 + -6

Combine like terms: 6 + -6 = 0
0 + -2x = 4 + -6
-2x = 4 + -6

Combine like terms: 4 + -6 = -2
-2x = -2

Divide each side by '-2'.
x = 1

Simplifying
x = 1

See similar equations:

| (3/8)-(2/10) | | (X-a)/(x-b) | | -19x-149=-12-86 | | 10x-32=6x-16 | | 2+3u=17 | | 0.09xX=67.87 | | 2(4x+9)-8x= | | 11x+110=6x+70 | | x-5=x+23 | | 7-3/4=x | | 5y-3=-38 | | -12x-86=-8x-54 | | -2x-11=-x-6 | | X^2-y^2=725 | | 14=2u+8 | | 18x+18=12x+12 | | (3x^2+x-5)(2x-7)= | | -2x+1=-x+2 | | m^2=11m-24 | | 3x-9x+6=20-3+4x | | -15x+19=-8x+12 | | 5x+8y=140 | | 16x-15=10x-9 | | (t-9)(t+36)=0 | | 7x^2+28x= | | 5x=9x-19 | | 10+5(x-2)=-4x+1 | | x(6x-10)=6x^2-60 | | sin^2(x)+cos^2(2x)=1 | | -2y=11+-6x | | 9x-2(3x-10)=23 | | -2y=11-6 |

Equations solver categories